Optimizing the microencapsulation of Lactobacillus salivarius LET 201 with soybean protein isolate and sodium alginate - Babot, Jaime Daniel (2022)
The use of antibiotics as animal growth promoters has been banned in many countries. Therefore, the search for new alternatives to replace these drugs in animal production has boomed in the recent years. Probiotics have the potential to replace the sub-therapeutic use of antibiotics in poultry rearing, though the detrimental conditions in the gastrointestinal tract of birds limit their application. The encapsulation of probiotics allows them to bypass such negative conditions and reach the intestine in a viable state. Nevertheless, these capsules should be small enough as to not alter the organoleptic properties of the feed. Thus, the aim of this study was the optimization of the encapsulation of the probiotic strain Lactobacillus salivarius LET 201 with soy protein isolate (SPI) and sodium alginate to obtain spheres with sizes in the order of the micrometers. To this end, the water in oil emulsion technique was employed for the microencapsulation. Different concentrations of SPI (0, 30, 60, and 100 mg/mL), sodium alginate (0, 0.2, and 1.0%), and gelling agent (0.01, 0.1, and 0.5 M CaCl2), as well as distinct agitation times (15, 30, and 60 min) and soybean oil nature (commercial versus raw) were tested. The morphology and diameter of the particles were assessed using a conventional microscope coupled with a camera and the Carl Zeiss AxioVision Software. The diameter of the microcapsules was not different in the range of 0 ? 60 mg/mL SPI (around 30 µm), although they were significantly bigger (p > 0.05) when 100 mg/mL SPI was tested. The size of the microcapsules was neither influenced by the alginate concentrations assayed, although in absence of the polysaccharide the particles presented irregular shape, and alginate granules were observed inside the spheres in presence of 1% alginate. Similarly, the concentration of CaCl2 showed no effect on the diameter of the microcapsules, although irregular particles and high size variability were observed when the lower and higher concentrations of salt were tested, respectively. Regarding the agitation time, significantly bigger microspheres were obtained for 60 min stirring. Moreover, the nature of the soybean oil employed showed no influence on the diameter of the particles. Considering these results, the following conditions were selected for the production of spherical microcapsules with approximately 30 µm diameter and little size dispersion: 60 mg/mL SPI, 0.2% sodium alginate, 30 min stirring, 0.1 M CaCl2, and commercial soybean oil. These results pave the way for the design of a probiotic product for poultry that includes beneficial bacteria that reach the intestine of the birds in a viable state.